The First French-Canadian National Parks: Kouchibouguac and Forillon in History and Memory - Rudin, Ronald (Journal of the Canadian Historical Association / Revue de la Société historique du Canada)

(untitled) (The Canadian Historical Association / La Société historique du Canada, 2011)
Until the mid-1970s, the creation of a national park in Canada meant the removal of the resident population whose presence was viewed as incompatible with the preservation of nature and its presentation to visitors. Like other high-modernist schemes of the time, park projects were conceived by agents of the state whose knowledge trumped that of the people on the ground whose lives were viewed as worthless. The first nineteen of Canada’s national parks were created in areas populated predominately by English-speakers so that it was only with the creation of Kouchibouguac National Park in New Brunswick in late 1969 and Forillon National Park in Quebec eight months later that French-speakers bore the brunt of forced removal. This essay explores the dynamics regarding the creation of the first two French-Canadian national parks, both of which emerged in the midst of révolutions tranquilles, one acadienne and the other québécoise. This context shaped both the process that led to the development of the parks and to the very different ways that they have been remembered over the past forty years.